O PROJETO DE IDENTIDADE NACIONAL NOS ROMANCES DE JORGE AMADO NOS ANOS 1930 - Basso, Lucas (2020)
This dissertation objective is to analyze Jorge Amado’s literary production in the 1930’s. The purpose is to caracterize his national identity project by his perception of the concepts of race and class, applied in the creation of archetype characters in his novels and also Amado’s activity as an intellectual of his time. At first, it becomes necessary to comprehend the state of the intellectual, literary and social fields of the 1930’s, since Amado’s work is a close dialogue with social, political and literary discussions of the decade studied in this dissertation. The analysis begins with the assumption that, in order to Amado create a national identity project, he utilized two key concepts: race and class, and that the author essentially used these notions as a foundation to his novels. Once the bases that legitimize Amado’s production are elucidaded, it is necessary an investigation about the final product of the national identity project and also its purpose and implications. The sources to be utilized in this dissertation, consist on the six novels written by Jorge Amado in the 1930’s decade, but also enterviews, letters, essays and other productions inside the studied period of time. This analysis will be accomplished by the Intellectual History and the History of Literature’s optic, on an effort to comprehend the literary field in which Jorge Amado was and built his intellectual legitimity, as well as analyze the dialogue between the author with the pairs and the way literature is managed as a tool for an intellectual intervention on the public world.